2016
DOI: 10.1111/tbj.12706
|View full text |Cite
|
Sign up to set email alerts
|

Fibroepithelial Lesions in the Breast of Adolescent Females: A Clinicopathological Study of 54 Cases

Abstract: Background Fibroepithelial lesions (FELs) are the most frequent breast tumors in adolescent females. The pubertal hormonal surge could impact the growth and microscopic appearance of FELs in this age group. In this study, we evaluate the morphology and clinical behavior of FELs in adolescents. Design We searched the 1992–2012 pathology database for FELs in females 18 years old or younger (F≤18y). Seven FELs from 1975–83 were also included. Three pathologists reviewed all available material. Patient (pt) char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 25 publications
2
23
0
1
Order By: Relevance
“…We noticed that the most mitotically active area is often only focal, confined to a single set of 10 HPF, especially in the low end of the spectrum. Increased mitotic index in fibroepithelial lesions has been described in pediatric and adolescent populations [21,22]. We also found that patients with fibroadenomas and benign phyllodes that had mitotic index outside of the expected range tended to be younger (the mean and median age of 30 years).…”
Section: Discussionsupporting
confidence: 65%
“…We noticed that the most mitotically active area is often only focal, confined to a single set of 10 HPF, especially in the low end of the spectrum. Increased mitotic index in fibroepithelial lesions has been described in pediatric and adolescent populations [21,22]. We also found that patients with fibroadenomas and benign phyllodes that had mitotic index outside of the expected range tended to be younger (the mean and median age of 30 years).…”
Section: Discussionsupporting
confidence: 65%
“…Interestingly, although fibroadenomas with a higher stromal mitotic count may be associated with an increased risk of recurrence, some studies have found conversely that phyllodes tumours with MED12 mutations have a lower risk of recurrence . Also, another study reported that stromal mitotic activity in paediatric fibroadenomas can be substantial, ranging up to seven per 10 high‐power fields, and caution against overdiagnosing phyllodes tumours …”
Section: Discussionmentioning
confidence: 99%
“…6,27,28 Also, another study reported that stromal mitotic activity in paediatric fibroadenomas can be substantial, ranging up to seven per 10 high-power fields, and caution against overdiagnosing phyllodes tumours. 29 One limitation of our study is that the stromal component of the fibroadenomas was not microdissected from the epithelial component before sending for targeted gene sequencing. As a result, the gene mutations that were found may not be entirely attributable to the stromal component of the tumour alone and could be possibly localised to the epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…However, phyllodes tumors share similar histological fashion with fibroadenomas, sometimes surgeons have to do needle biopsy to preclude malignant phyllodes tumor, which requires a wider excision than fibroadenomas. Though Ross et al hold the view that morphologic features of fibroepithelial lesions should be diagnosed cautiously in adolescents, especially to avoid over diagnosis of phyllodes tumor, which might lead to unnecessary and potentially disfiguring surgery. On the other hand, a review of malignant breast cancer in children reported that most childhood phyllodes tumors are benign .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, no treatment guidance was provided for GJF. In some previous reports, the patients were treated with only simple surgical resection alone, as referenced by Sosin et al breast reconstruction was completed in 27 out of 153 cases (17.6%) . However, considering the removal of a large fibroadenoma (more than 2000 g) may significantly affect the shape of the breast, it is necessary to perform immediate or delayed breast reconstruction.…”
Section: Introductionmentioning
confidence: 99%